Dampak Moderasi Moral Perpajakan pada Hubungan Perceived Probability of Audit dan Sanksi terhadap Perilaku Kepatuhan Pajak Usaha Mikro, Kecil dan Menengah (UMKM) - Riri Zelmiyanti; Eko Suwardi (Pusat P2M Politeknik Negeri Batam, 2019)
This study aims to explore more carefully and in detail the influence of economic factors (perceived probability of audits and sanctions) and behavioral factors (moral) of the tax compliance of SMEs in Indonesia. Research on tax compliance has been done, but still a bit that combines economic and behavioral factors. Previous research mostly done on large companies and to individual taxpayers. The current study was conducted on SME entrepreneurs. This study tried to moderate the tax morale in relation to perceived probability of audits and sanctions against tax compliance. Samples in this study were individual taxpayers from SMEs in Yogyakarta. The research data was collected through a survey. Questionnaires had been processed in this study were around 118 questionnaires. Testing the hypothesis in this study used multiple regression analysis and analysis regression moderated. Regression analysis tool used is IBM SPSS 19.0. The results of this study indicate that the perceived probability of audits and sanctions have a direct impact on tax compliance. This study was not able to prove the moral moderating effect of taxation on the relationship perceived probability of an audit of tax compliance. This study also can not prove the moral moderating effect of taxation on the relationship sanctions on tax compliance.